ANALISIS NILAI MECHANICAL PROPERTIES GAS TUNGSTEN ARC WELDING (GTAW) PADA MATERIAL STAINLESS STEEL 304 DENGAN VARIASI HEAT INPUT MENGGUNAKAN METODE NDT - Widodo, Agus; Rivandi, Merdieco; Prasetiyo, Joko (Jurnal Inkofar, 2023)
ABSTRACTPT. XYZ is a company engaged in industrial gas, gas installation, tank / iso tank service, and various kinds of equipment related to industrial gas. Based on the source of the report data from thesection, workshop there is a fabrication process for industrial gas installations which often occurs in defects in the welding process which often results in failure in welding tests. The cause of welding defects can be due to incorrect welding procedures, inadequate preparation and can also be caused by equipment and consumables that do not meet standards. So, based on this, a research with the title. "Analysis of Mechanical Properties of Gas Tungsten Arc Welding (GTAW) onMaterial Stainlees Steel 304 with Variation of Heat Input using themethod NDT at PT. XYZ. The test method that is often carried out at PT CYZ is themethod non-destructive test (NDT) using dye penetrant. Therefore, the method used in this research is the dye penetrant test. This welding test will not damage the results of the weld so that the welding defects that occur can be seen clearly and can be repaired. The purpose of NDT activities include detecting defects or discontinuity (above the surface, below the surface, and within a material), to measure the geometry of objects, and determine the chemical composition of the material. The result of this research is that the heat input of each specimen is influenced by the factors of current, voltage and welding speed. This is related to the welding speed on each specimen, where the welding speed is influenced by the welding time. Specimens given the highest current input have less welding time, this is because the process of melting filler metal and base matal is faster when compared to giving a low current input. It can be seen in specimens A and C in this study that welding defects have occurred, this occurs because the welding current welding process must be adjusted to what stages will be carried out, because each welding stage has a different seam thickness.  Keyword: Stainless steel 304, GTAW, Heat Input, NDT Dye Pentrant Test